Pengaruh Lama Pencucian Terhadap Kadar Vitamin B1 Pada Beras Putih Dan Beras Merah Secara Spektrofotometer Visibel - Roslinda Rasyid; Anisa Nurul Fitria; Humaira Fadhilah (STIFARM Padang, 2014)
A research about analysis of vitamin B1 on the effeccts of long leaching on levels of vitamin B1 on white rice and red rice using UV-Visible spectrophotometry. Vitamin B1 reacted with bromthymol blue for compose ion-association complex. For improve solubility of Vitamin B1 complex compounds with bromthymol blue be added polivinyl alcohol as a solubilization substance, and added amonia buffer as pH buffer, that measured with wavelength of maximum absorbance was 431,0 nm. Average (%) Vitamin B1 level of white rice after leaching minutes 1 is 0,0166. Average vitamin B1 level of red rice after leaching minutes 1 is 0,0262. The highest level of vitamin B1 from the white rice and red rice was found on minute 1 after leaching. From the statistical analysis one way ANOVA using SPSS 17 program found a significant difference (p<0,05) from each sample.